SIMULASI PENGOPTIMALAN WAKTU MEMASAK BUAH KELAPA SAWIT DENGAN LOGIKA FUZZY - Wenda, Yesi Hairian (Menara Ilmu, 2017)
Simulation is a technique to imitate the operations or processes - processes that occur in a system with the help of computer equipment and based on certain assumptions that thesystem can be studied scientifically useful to facilitate in solving a problem. In designing thissystem using fuzzy logic mamdani. This research focused to know the cooking time by twopalm fruit input variables. The first input is a lot of oil in a fuzzy set is grouped into threenamely, small, medium, and a lot. As the second input is a great pressure of water vapor whichis divided into three fuzzy sets are small, normal, and large. As the output variable is the timeto cook the fruit in the palm of krlompokan into three fuzzy sets namely, fast, medium andslow. In this simulation design used fuzzy logic matlab mamdani with the help of software. Keywords: fuzzy logic, quick learning fuzzy logic, fuzzy logic applications, Simulation